The Influence of Parenting Methods on the Cognitive Development of Children Aged 5-6 Years - Suwarni Wati; Khairul Azmi; Mariawati Mariawati (Insights: Journal of Primary Education Research, 2024)
The purpose of this study is to ascertain how parenting styles affect the cognitive development of five- and six-year-old students at PAUD HASANI in the 2022–2023 school year. Experimental research using a one-group pretest-posttest design is used in this kind of study. The fifteen children who made up the study's population were all between the ages of five and six. Saturated sampling was used to determine the research sample. Documentation and observation are two methods used in data collection. T-test is used in data analysis techniques. An observation sheet on children's cognitive development between the ages of five and six served as the instrument. The study's findings indicated that the child's overall cognitive development at the pretest was 218 with an average percentage of 36% and an assessment category of Starting to Develop (MB). Following treatment, the child's overall cognitive development was 457 with an average of 76% and an assessment category of Very Well Developing (BSB) following a posttest. In addition, the tcount hypothesis test results, which are 22.6309 with a value of 1.761, demonstrate that the outcomes of the hypothesis analysis in this study are accepted and rejected. This is demonstrated by the value of tcount(22.6309) > (1.761). In conclusion, throughout the 2022–2023 school year, the use of parenting techniques affects the cognitive development of children at PAUD HASANI who are between the ages of 5 and 6.